Mortality in a cohort of patients with psychogenic non-epileptic seizures. Issue 7 (4th June 2012) - Duncan, Roderick; Oto, Meritxell; Wainman-Lefley, Jessica
Abstract : Some evidence suggests that psychogenic non-epileptic seizures (PNES) are associated with increased mortality. The authors obtained death certificate information in a cohort of 260 patients who presented with PNES between 1999 and 2004. The follow-up period averaged 7.92 years, during which 17 patients died, 12/17 were under the age of 75 years, giving a premature (<75 years) mortality rate of 0.58%, compared with a Scottish mortality rate for the 40–75 years age group of 0.41% per year. The main predictor of death was the patient age at presentation of PNES. There was no correlation with withdrawal of anticonvulsant medication, and death certificate information provided no evidence to suggest that the deaths were related to the seizure disorder. The population had a high mean deprivation rank, providing a possible explanation for a modest increase in premature death rate.